6-6x-3=-4+3x-11

Simple and best practice solution for 6-6x-3=-4+3x-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-6x-3=-4+3x-11 equation:


Simplifying
6 + -6x + -3 = -4 + 3x + -11

Reorder the terms:
6 + -3 + -6x = -4 + 3x + -11

Combine like terms: 6 + -3 = 3
3 + -6x = -4 + 3x + -11

Reorder the terms:
3 + -6x = -4 + -11 + 3x

Combine like terms: -4 + -11 = -15
3 + -6x = -15 + 3x

Solving
3 + -6x = -15 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
3 + -6x + -3x = -15 + 3x + -3x

Combine like terms: -6x + -3x = -9x
3 + -9x = -15 + 3x + -3x

Combine like terms: 3x + -3x = 0
3 + -9x = -15 + 0
3 + -9x = -15

Add '-3' to each side of the equation.
3 + -3 + -9x = -15 + -3

Combine like terms: 3 + -3 = 0
0 + -9x = -15 + -3
-9x = -15 + -3

Combine like terms: -15 + -3 = -18
-9x = -18

Divide each side by '-9'.
x = 2

Simplifying
x = 2

See similar equations:

| 12y^5+4y^4-10y^3=0 | | -2y^2-9=-11y | | 9(2w+4)+9w= | | 5k+1=4K-11 | | -2+2x=-(4-3x) | | 12(7m+2)=6(4m-7) | | -2(n-1)=10-n | | 20f+14=13f+35 | | 3(5x-3)=51 | | 3G-6g(g-8)=42 | | 4x+5-3=5x-3x+12 | | 4x+1-6x+3+2= | | -6a-34=-5(1+7a) | | 4(r-3)=2(r+8) | | 3x-5=9x-17 | | q=11200-100p-1960 | | 3a+2=a+7 | | -2Ax^2+2Ax+2A-2Bx+b-2C=x^2 | | 27-w=14 | | x=15*90 | | 2s+2=134 | | 6x+9x-22=66-7 | | 5(3x-9)-8=5(x-3)+32 | | (2x-5)(2x-4)=0 | | q=9240-100p | | F(1)=2x-4 | | 10p^2-13p+5=0 | | -4.7v-44.2=-8.3v | | v=523.6*.75 | | 2x-18=-x+24 | | 5x+4x=-9 | | 12-9y-45=-1+y |

Equations solver categories